A Safe Method for Early Rehabilitation of Articular Fracture at the Base of Thumb Metacarpal Bone - Yunus Oc; Bekir Eray Kilinc; Ali Varol; Adnan Kara (Advances in Orthopedics)
Background. To evaluate the clinical and radiological results of closed reduction, distraction using an external fixator, and percutaneous fixation in patients with Bennet and Rolando fractures. Methods. Patients over 18 years of age, who had isolated fracture at the base of the first metacarpal bone, had no previous functional limitations and pain complaints, were regularly followed up, and had fixation using K-wire combined with an external fixator, were included. Arthrosis was evaluated according to Eaton and Littler classification. Pain intensity was evaluated using the visual analogue scale (VAS) on a 0–10 scale. Furthermore, patients were questioned regarding limitations in their daily activities and hobbies. Pinch and grasp strengths were evaluated. Results. Thirteen of the patients were male and five were female, with a mean age of 31.5 ± 12.5 years. The surgical procedure was performed on the right extremity in 12 patients and left extremity in six patients. Twelve patients were found to have Bennet fractures, whereas six patients had Rolando fractures. The mean follow-up period of the patients was found to be 29.6 ± 5.4 months. The VAS score was rated as 2 in one patient and 1 in one patient. Other patients had a pain VAS score of 0. The mean Quick-DASH score was calculated to be 1.20. No statistical difference was found in pinch strength between the two extremities (p > 0.05). No difference was observed in terms of the range of motion (p > 0.05). Conclusion. Fixation using K-wire combined with an external fixator has more benefits than its disadvantages and is superior to other methods in the intra-articular fractures of the first metacarpal bone.